Enhancement of laser-driven betatron x-rays by a density-depressed plasma structure. (10th January 2019) - Guo, B; Cheng, Z; Liu, S; Ning, X N; Zhang, J; Pai, C H; Hua, J F; Chu, H H; Wang, J; Lu, W
Abstract: We report a significant enhancement of betatron radiation from a laser wakefield accelerator (LWFA) by inserting a density-depressed plasma structure. By using a technique of transverse laser machining, a longitudinally density-depressed plasma structure with tunable length and position has been fabricated to increase the betatron amplitude of the electron beam in the LWFA, leading to an enhanced photon number and critical energy of the betatron x-ray beam. By adjusting the length and position of the plasma density depression region, the photon number of the betatron x-ray is enhanced by a factor of 3, and the critical energy is enhanced by a factor of 1.4.